Does Zakat Management Organization Comply with PSAK 109? - Novie Andriani Zakariya; Syam, Nur; Ahsan, Muhamad; Arifin, Sirajul; Ilham, Moh (Proceedings of International Conference on Da'wa and Communication, 2023)
Abstract: The purpose of this study is to analyze the compliance of Zakat Management Organizations (ZMO) in Indonesia with financial accounting Statement of Financial Accounting Standards (PSAK) 109. This study uses the literature review study method, where the source of this database is obtained from trusted scientific searches from the range of 201 8-2022 national journals. This literature study was conducted by collecting 15 references to trusted scientific research journal data related to compliance with the Statement of Financial Accounting Standards (PSAK) 109 concerning Zakat, Infak and Alms Accounting at Zakat Management Organizations (ZMO) in Indonesia. The results of this study researchers found that there are 3 typologies in compliance with the application of the Statement of Financial Accounting Standards (PSAK) 109 concerning Accounting for Zakat, Infak and Alms in Zakat Management Organizations in Indonesia, including: (1) Full Compliance, (2) Not Complete Compliance, (3) No Compliance. The highest category is in the third category that there are 6 Zakat Management Organizations that fall into the typology of no compliance with the Statement of Financial Accounting Standards (PSAK) 109 concerning Accounting for Zakat, Infak and Alms in Zakat Management Organizations (ZMO) in Indonesia.